Pendekatan Demokrasi Kyai Dalam Membangun Disiplin Santri Di Pondok Pesantren Al Mumtaz Tangerang - Solihin, Solihin (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2025)
Al Mumtaz Islamic Boarding School is known as an Islamic educational institution that implements the kyai's democratic parenting approach in educating its students. This approach emphasizes two-way interaction between kyai and santri, which encourages active involvement of santri in the learning process. Discipline is a very important aspect in pesantren education, because it can shape the character and morals of students. This study aims to examine the contribution of the kyai's democratic parenting model in building santri discipline at Al Mumtaz. This research uses a qualitative approach with a case study method. Data collection was conducted through in-depth interviews with kyai, pesantren administrators, and santri, as well as direct observation in the pesantren environment. Data analysis was conducted using a thematic approach to identify important elements of the kyai's democratic parenting that influence santri discipline. In addition, source triangulation was used to ensure data validity. The results showed that the application of the kyai's democratic parenting style in Al Mumtaz provides opportunities for santri to be involved in decision-making, so that they feel more responsible for their actions. This involvement strengthens discipline, because santri understand the consequences of every decision made. In addition, open communication between kyai and santri creates a supportive atmosphere, where santri can express opinions and input, which in turn fosters mutual respect and discipline.